Key indicators for Asia and the Pacific 2019. ([Manila] Asian Development Bank, 2019)
The Key Indicators for Asia and the Pacific 2019, the 50th edition of this series, presents the latest statistics on a comprehensive set of economic, financial, social, environmental, and SDG indicators for the 49 regional members of the Asian Development Bank (ADB). It is designed to serve as a resource for information on development issues across the region for a wide audience, including policy makers, development practitioners, government officials, researchers, students, and the general public. The new Key Indicators Database allows interactivity with the data in a user friendly manner. The database advanced functionality includes a categorized search facility for data, various download options, and customized data visualization.
Keywords: Economics; Poverty; Electronic book